The Best Interest of the Child of Double Burden Crime Perpetrators from the Perspective of the Juvenile Criminal Justice System (UU SPPA) - Enggenia Delin Raradela; Yusep Mulyana; Oki Earlivan Sampurno (International Journal of Social Sciences and Humanities, 2026)
This study examined the application of the best interest of the child principle in cases of double burden crime sexual assault combined with murder committed by a child perpetrator against a child victim under Indonesia's Juvenile Criminal Justice System (Law No. 11 of 2012). The research employed a juridical-normative method using statutory, case, and conceptual approaches, with Verdict No. 50/Pid.Sus-Anak/2024/PN.Plg as the primary object of analysis. Findings revealed that the Law established a multi-layered sentencing limitation system, including a maximum imprisonment ceiling of ten years for the most serious offenses, yet this framework was not designed to accommodate double burden scenarios. The application of the best interest principle in the examined verdict was procedurally satisfied but created a structural blind spot toward the child victim's rights, resulting in an imbalanced fulfillment of the four dimensions of punishment: retribution, general deterrence, specific deterrence, and societal protection. This study concluded that policy reforms were necessary, including reformulation of the maximum sentencing provision for double burden cases, strengthening of a double track system combining imprisonment and rehabilitation, integration of mandatory restitution, and issuance of judicial guidelines as a short-term measure to reduce sentencing disparities.